R.E.N.A.L. nephrometry score in clinical stage T1 renal mass: Ramathibodi hospital experience - Sirianan Prasit (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: The main treatment strategies for clinical stage T1 renal mass are radical nephrectomy (RN) and partial nephrectomy (PN). Treatment decision depends largely on tumor complexity as assessed by the R.E.N.A.L. nephrometry scoring system. The authors evaluated our experience with R.E.N.A.L. nephrometry score in all patients who underwent surgery. Material and Method: The authors evaluated 61 patients who presented with clinical stage T1 renal mass and underwent radical or partial nephrectomy between 2007 and 2013 at Ramathibodi Hospital. Tumor complexity was quantified by R.E.N.A.L. nephrometry score in all patients using preoperative imaging. Statistical analysis was done to study associations. Results: Sixty-one patients were included in this study, which 34 (55.70%) were male and 27 (44.30%) were female. The most common pathologic report was clear cell renal cell carcinoma followed by angiomyolipoma and papillary renal cell carcinoma. Forty-one patients underwent radical nephrectomy, of whom three, 25, and 10 patients had low, moderate, and high tumor complexity, respectively. Twenty patients underwent partial nephrectomy, of whom 10 patients had low tumor complexity and 10 patients had moderate tumor complexity. No patient had high tumor complexity. In the present study, the function coefficient showed that radius had the most influence on surgical decision-making, followed by nearness to collecting system, exophytic/endophytic, and location. We also developed the Ramathibodi equation to help selecting the proper operation. Conclusion: The R.E.N.A.L. nephrometry score is a feasible and standardized classification system for evaluating renal masses. It could be used to stratify tumor complexity and may help for surgical decision-making.